The Implementation Of Essay Grading To Analyze Concept Understanding Profile Of Heat And Temperature - Dewi Ratnasari; S Sukarmin; Suparmi Suparmi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
The aim of this research is to analyse concept understanding profile of heat and temperature by applying essay grading technique. This research is a descriptive research using quantitative approach. The subjects of the research are 10th-grade students in Surakarta academic year of 2016/2017. The number of samples was 95 students. Sample selection technique used purposive sampling that selected students from high, medium and low categorised school. Data were collected from test and interview. Before the questions were tested to the research subjects, the essay questions were validated by experts. Based on the result and data analysis, concept understanding profile of 10th-grade students in Surakarta on heat and temperature as follows: 6,32% students in the high category, 42,11% in an adequate category, 45,26% students in a low category is and 6,32% in the very low category.